Tratamiento contable en los estados financieros de la empresa el Dorado S.A, según la norma internacional de contabilidad 1. - Benitez Maldonado, Edison Geovanny (My University, 2018)
The present investigation was developed with the objective of structuring the statement of results and balance sheet through the analysis of information for making the right decisions in the company. The financial statements are considered of great importance for the companies, since through the results they show, it is possible to formulate and implement strategies that contribute to the improvement of their activities, thus offering a reliable information that allows the correct decision making by the parties. of its managers and administrators. The methodological research considers the qualitative and quantitative approach to be carried out, also supporting the bibliographic review, systemic, inductive and deductive method, the same ones that supported this work. The analysis and interpretation of results of the financial statements is very important, because through them, it is possible to know the composition of the assets, liabilities and equity accounts, income and expenses. In fact, all companies have the need to perform and interpret the financial statements with the application of the International Accounting Standards IAS 1, in which its structure is detailed together with the financial indicators. The results obtained in the investigation denote that the company El Dorado S.A. presents an adequate usefulness and stable financial situation; part of the current assets is financed with current liabilities, which means that the company has sufficient liquidity to face its immediate debts, either in the short or long term.
La presente investigación se desarrolló con el objetivo de estructurar el estado de resultados y balance general mediante el análisis de información para la toma de decisiones acertadas en la empresa. Los estados financieros se consideran de gran importancia para las empresas, ya que a través de los resultados que arrojan, es posible formular e implementar estrategias que contribuyan al mejoramiento de sus actividades, ofreciendo así una información fidedigna que permita la toma de decisiones acertadas por parte de sus directivos y administradores. La investigación metodológicamente considera para su realización el enfoque cualitativo y cuantitativo, apoyándose además de la revisión bibliográfica, método sistémico, inductivo y deductivo, los mismos que sustentaron este trabajo. El análisis e interpretación de resultados de los estados financieros es de suma importancia, debido que, a través de ellos, es posible conocer la composición de las cuentas de activo, pasivo y patrimonio, ingresos y gastos. De hecho, todas las empresas tienen la necesidad de realizar e interpretar los estados financieros con la aplicación de las Normas Internacionales de Contabilidad NIC 1, en la que se detalle su estructura conjuntamente con los indicadores financieros. Los resultados logrados en la investigación denotan que la Empresa El Dorado S. A. presenta una adecuada utilidad y situación financiera estable; parte del activo corriente se financia con pasivo corriente, lo que significa que la empresa tiene liquidez suficiente para hacer frente a sus deudas inmediatas ya sea a corto o largo plazo.
Keywords: TOMA DE DECISIONES; ANÁLISIS E INTERPRETACIÓN; ESTADOS FINANCIEROS